Review of subfamily Prodiamesinae (Diptera: Chironomidae) from the Russian Far East and bordering territory - Makarchenko, Eugenyi A.; Semenchenko, Alexander A. (Zootaxa, 2023)
Based on material from the Russian Far East and Eastern Siberia, a revision of the chironomids of the subfamily Prodiamesinae was carried out. A new species Monodiamesa fontinalis sp. nov., is here described, ten species from four genera—Monodiamesa bathyphila Kieffer, M. kamora Makarchenko et Yavorskaya, M. improvisa Makarchenko, M. nitida Kieffer, Odontomesa fulva Kieffer, Prodiamesa levanidovae Makarchenko, Propsilocerus amurensis Makarchenko, P. jacuticus (Zvereva), P. paradoxus Lundström and P. taimyrus Zelentzov are redescribed with varying degrees of completeness. Propsilocerus taimyrus Zelentzov, 2000 is proposed as senior synonym of P. saetheri Wang, Liu et Paasivirta, 2007. DNA barcoding of four species, M. fontinalis sp. nov., M. bathyphila, P. olivacea Meigen and P. akamusi (Tokunaga) was provided. Species delimitation and phylogenetic relationships using COI DNA barcodes confirms the species validity of M. fontinalis sp. nov.